The direct influence of psychological factors on international tourists' cognitive image of Bangladesh - Hai, Md Abdul (2014)
Tourism is said to be potentially vital for the economic development of Bangladesh. However, its poor image could be the reason for its slow growth. Literatures on destination image tell very little about the relationship between the tourists’ psychological factors and the cognitive image they have toward a destination that they visit. To fill this gap, this study examines the influence of tourists’ lifestyle, motivation, personality, and attitude towards service quality on cognitive image they have toward a destination, namely Bangladesh. This study, which is based on image formation theories and models, was carried out to achieve the following objectives: to examine the influential role of lifestyle on the cognitive image; to examine the influence of motivation on the cognitive image; to investigate the influence of personality on the cognitive image; to investigate the influence of tourists’ attitudes toward service quality on the cognitive image that tourists have toward Bangladesh; and to examine the variation of the cognitive image based on their socio-demographic factors such as gender, age, country of origin, education and income. To achieve the objectives of the study, data were collected from 600 international respondents in Bangladesh in 2012, yielding approximately 75% response rate. Exploratory factor analysis was initially used to assess the dimensionality of the various constructs in the theoretical model; thereafter correlation and multiple regression analysis were performed to investigate the relationship between lifestyle, motivation, personality, attitude towards service quality, and the cognitive image. In addition, the variation of the cognitive image based on socio-demographic variables was tested using ANOVA and t-test. The results indicated that the cognitive image held by tourists towards Bangladesh was influenced by their lifestyle, motivation, attitude towards service quality, and varied by country of origin and income. However, the study found no significant relationship between personality, gender, age, education and the cognitive image. Based on these findings, important practical and theoretical implications for destination image, product developments as well as destination marketing are highlighted.